AGE-RELATED AND LOCATION PECULIARITIES OF TOOTH ENAMEL RESTITUTION - А. А. Udod; А. S. Voronina (Український стоматологічний альманах)
Annotation. Relevance of the topic. Structural and functional acid resistance of enamel is evaluated by the test of resistance enamel, the essence of which is to assess the staining intensity of the enamel portion of the upper central incisor in equator area after pre-dosed acid exposure. Then occurs restoration (restitution) of the structure of the enamel area, which can be determined by the clinical estimation test of enamel remineralization rate. This process proceeds differently on different areas of the enamel.